Preparation method and application of recycled concrete micro powder for porous geopolymer material

By carbonizing the recycled concrete fine powder and mixing it with fly ash to prepare spherical porous polypolymers, the problem of difficult utilization of recycled fine powder and poor Pb2+ pollution treatment effect is solved, and the effect of efficient resource utilization and environmental governance is achieved.

CN119797824APending Publication Date: 2025-04-11XINJIANG HENGTAI ZHUYUAN NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510013174.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize recycled concrete fine powder, and the treatment effect of Pb2+ pollution is not ideal, and there are problems of waste of resources and environmental pollution.

Method used

Spherical porous regenerated powder-fly ash earth polymer is prepared by carbonizing the regenerated powder and mixing it with fly ash and other raw materials, and the adsorption effect on Pb2+ is improved using its porous structure and chemical composition.

Benefits of technology

It has achieved efficient resource utilization of waste concrete recycled fine powder, reduced environmental pollution, improved the adsorption stability and efficiency of Pb2+, and achieved the environmental protection goal of "dirty pollution control with waste".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797824A_ABST
    Figure CN119797824A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building solid waste resource utilization, in particular to a preparation method and application of recycled concrete micro powder for a porous geopolymer material. The preparation method comprises the steps that 1, carbonized recycled micro powder is prepared; 2, preparing raw materials; 3, mixing the raw materials; step 4, balling and curing; step 5, washing and roasting; step 6, final washing; according to the preparation method and application of the recycled concrete micro-powder for the porous geopolymer material, the recycled micro-powder is carbonized and mixed with the raw materials such as the fly ash to prepare the spherical porous recycled micro-powder-fly ash geopolymer, so that resource utilization of waste resources is facilitated, and waste of the resources is avoided; meanwhile, the stability and high efficiency of adsorption are effectively improved, Pb < 2 + > can be efficiently removed from a water body, the environmental protection target of treating pollution with waste is achieved, and therefore the health of the environment and human beings is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource utilization of construction solid waste, and in particular to a preparation method and application of recycled concrete micropowder for porous geopolymer materials. Background Art

[0002] In the construction industry, the treatment of waste concrete is a highly concerned issue. After treatment, it will produce two types of products: recycled aggregate and recycled concrete powder. At present, the treatment and application of recycled aggregate has been relatively perfected, which can achieve better resource reuse; however, the corresponding research on recycled concrete powder is still in the development stage and there are some shortcomings.

[0003] On the one hand, as far as the resource utilization of recycled concrete powder is concerned, its added value is generally not high. In the existing application methods, most of them are just added to cement as a supplementary cementitious material, but this method has strict restrictions. When the replacement rate of recycled powder exceeds 30%, it will have an adverse effect on the quality of concrete, which is not conducive to the efficient resource utilization in a larger range, resulting in a large amount of recycled powder resources being idle and wasted;

[0004] On the other hand, in the field of environmental pollution control, Pb 2+ As one of the most serious elements in my country's heavy metal pollution, it poses a serious threat to human health due to its non-biodegradability, high toxicity and carcinogenicity. Even at low concentrations, it cannot be ignored. 2+ Although there are many pollution treatment technologies, such as chemical precipitation, electrolysis, ion exchange, bioremediation and adsorption, they still have their own limitations. For example, chemical precipitation may produce a large amount of sludge that needs to be treated later; electrolysis has high energy consumption; ion exchange resin regeneration is complicated and costly; bioremediation is greatly affected by environmental conditions and has a long repair cycle; in the adsorption method, the existing adsorbents are either expensive or have unsatisfactory adsorption effects, which not only reduces the efficiency of environmental pollution control, but also makes Pb 2+ The pollution treatment effect is reduced, and the stability and reliability of the treatment effect are also reduced, resulting in the increase of Pb in environmental media such as water bodies. 2+ It is difficult to remove in a sustainable and stable manner, thus affecting the environment and human health.

[0005] In view of this, there is an urgent need for a preparation method and use of recycled concrete powder for porous geopolymer materials. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a porous geopolymer material using recycled concrete powder and its use, so as to solve the problems raised in the above-mentioned background technology.

[0007] To achieve the above object, on the one hand, the present invention provides a method for preparing a porous geopolymer material using recycled concrete fine powder, comprising the following steps:

[0008] S1. Preparation of carbonized regenerated micropowder: placing the regenerated micropowder in a tube furnace, then introducing a CO2 atmosphere with a concentration exceeding 99.5% into the tube furnace, opening the tube furnace for roasting, and after the roasting is completed, closing the carbon dioxide gas source, and taking out the powder after naturally cooling it to room temperature in the tube furnace to obtain carbonized regenerated micropowder;

[0009] S2. Raw material preparation: carbonized regenerated micro powder; fly ash; liquid sodium silicate; sodium hydroxide; distilled water; foaming agent; modulus adjustment;

[0010] S3, raw material mixing: fly ash, carbonized regenerated powder, liquid sodium silicate, sodium hydroxide, distilled water and foaming agent are added to a stirring container in sequence, and the stirring container is opened to stir and mix to obtain a mixed slurry;

[0011] S4, balling and solidification: Turn on the water bath device for heating, and prepare a container for silicone oil. Then, use a syringe to drop the mixed slurry into the silicone oil to make it into small balls with uniform shape, and solidify the small balls in the silicone oil;

[0012] S5, washing and calcining: taking the solidified balls out of the silicone oil, washing them in anhydrous ethanol, and then calcining them in a muffle furnace to remove the silicone oil in the pores of the balls. After calcining, turning off the power of the muffle furnace and allowing the balls to cool naturally to room temperature in the furnace;

[0013] S6. Final washing: The calcined pellets are placed in deionized water for soaking and washing. After the soaking and washing is completed, the pellets are taken out from the deionized water and dried naturally to finally obtain spherical porous regenerated micropowder-fly ash geopolymer.

[0014] As a further improvement of the technical solution, in S1, after the temperature of the tube furnace is raised to 300° C., the roasting is continued for 2 hours.

[0015] As a further improvement of the technical solution, S2 includes the following raw materials in amounts:

[0016] Carbonized regenerated micro powder: The dosage of carbonized regenerated micro powder is 3g-5g;

[0017] Fly ash: The amount of fly ash is 5g-7g;

[0018] Liquid sodium silicate: The dosage of liquid sodium silicate is 1.5g-2.5g;

[0019] Sodium hydroxide: The dosage of sodium hydroxide is 0.15g-0.27g;

[0020] Distilled water: The amount of distilled water used is 1.1ml-2.2ml;

[0021] Foaming agent: Mix silicon slag and K12 in a dry and clean environment. The amount of silicon slag is 0.3g-0.5g, and the amount of K12 is 0.035g-0.045g;

[0022] Modulus adjustment: M=1.4.

[0023] As a further improvement of the present technical solution, in S3, the stirring speed of the stirring container is 180r / min-240r / min, and the stirring time is 20min-30min.

[0024] As a further improvement of the technical solution, in S4, the water bath is heated to 75°C.

[0025] As a further improvement of the technical solution, in S4, the injection speed of the syringe into the mixed slurry is 0.5ml / min-1ml / min.

[0026] As a further improvement of the technical solution, in S4, the beads are cured in silicone oil for 1 hour.

[0027] As a further improvement of the technical solution, in S5, the number of times the beads are washed is 3-4 times, and each washing time is 8 minutes to 12 minutes.

[0028] As a further improvement of the technical solution, in S5, the muffle furnace is preheated to 300° C. for roasting, and the roasting time is 1 hour.

[0029] On the other hand, the present invention provides an application of recycled concrete powder for porous geopolymer materials. The spherical porous recycled powder-fly ash geopolymer obtained by the above-mentioned method for preparing recycled concrete powder for porous geopolymer materials is used to treat Pb in the environment. 2+ pollute.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The preparation method and use of the recycled concrete powder for porous geopolymer material, by carbonizing the recycled powder and mixing it with fly ash and other raw materials to prepare spherical porous recycled powder-fly ash geopolymer, is not only conducive to the resource utilization of waste resources, avoiding the waste of resources, but also reducing the pressure that these wastes may cause to the environment, and at the same time, effectively improving the adsorption stability and efficiency, and being able to efficiently convert Pb 2+ It is removed from water bodies, achieving the environmental protection goal of "using waste to treat pollution", thereby improving the health of the environment and humans.

[0032] 2. The recycled concrete powder is used in the preparation method and use of porous geopolymer materials. The spherical porous recycled powder-fly ash geopolymer has a great influence on the degradation of Pb 2+ It has good adsorption effect. Its layered gel structure is densely covered with continuous pores, which greatly increases the specific surface area and provides more active sites. In addition, the carbonization treatment improves the regenerated micropowder's adsorption of Pb 2+ Active sites, during the adsorption process, the chemical composition and structural characteristics of the material can effectively adsorb Pb 2+ , reducing the cost of materials, not only can it achieve the effective utilization of recycled micro-powder from waste concrete, but it can also transform the original waste into an adsorbent that is beneficial to environmental governance, realizing the “turning waste into treasure”, thereby improving the utilization rate of waste resources and the efficiency of environmental restoration. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a flowchart of the method for preparing porous geopolymer material using recycled concrete powder according to the present invention;

[0034] Figure 2 This is the surface morphology image of the electronic scanning electron microscope of the present invention;

[0035] Figure 3 This is the SEM-EDS characterization diagram of the present invention;

[0036] Figure 4 is the XRD pattern of the material of the present invention;

[0037] Figure 5 : is the nitrogen adsorption-desorption isotherm of the material of the present invention, and the embedded figure is the pore radius distribution diagram determined by the BJH method. DETAILED DESCRIPTION

[0038] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0039] Example

[0040] according to Figure 1 As shown, an embodiment of the present invention provides a method for preparing a porous geopolymer material using recycled concrete powder, comprising the following steps:

[0041] Step 1, preparation of carbonized regenerated micropowder: placing the regenerated micropowder in a tube furnace, then introducing a CO2 atmosphere with a concentration exceeding 99.5% into the tube furnace, opening the tube furnace for roasting, and after the temperature of the tube furnace rises to 300°C, continuing the roasting for 2 hours. After the roasting is completed, turning off the carbon dioxide gas source, and taking out the carbonized regenerated micropowder after naturally cooling to room temperature in the tube furnace to obtain the carbonized regenerated micropowder;

[0042] Step 2: Raw material preparation: carbonized regenerated micro powder; fly ash; liquid sodium silicate; sodium hydroxide; distilled water; foaming agent; modulus adjustment; wherein:

[0043] Carbonized regenerated micro powder: The dosage of carbonized regenerated micro powder is 4g;

[0044] Fly ash: The amount of fly ash is 6g;

[0045] Liquid sodium silicate: The dosage of liquid sodium silicate is 2g;

[0046] Sodium hydroxide: The amount of sodium hydroxide used is 0.21g;

[0047] Distilled water: The amount of distilled water used is 1.6 ml;

[0048] Foaming agent: Silicon slag and K12 (sodium dodecyl sulfate) are mixed in a dry and clean environment. The amount of silicon slag is 0.4g and the amount of K12 is 0.04g.

[0049] Modulus adjustment: M = 1.4;

[0050] Step 3, mixing raw materials: adding fly ash, carbonized regenerated powder, liquid sodium silicate, sodium hydroxide, distilled water and foaming agent to a stirring container in sequence, opening the stirring container for stirring and mixing, the stirring speed of the stirring container is 180r / min-240r / min, and the stirring time is 20min-30min to obtain a mixed slurry;

[0051] Step 4: Spheroidization and curing: Turn on the water bath device for heating, heat the water bath device to 75°C, and prepare a container for silicone oil. The amount of silicone oil can cover the small balls to be formed, and the silicone oil is clean and free of impurities. Then, use a syringe to drop the mixed slurry into the silicone oil. The injection speed of the syringe to the mixed slurry is 0.5ml / min-1ml / min, so that it becomes small balls with uniform shapes, and the small balls are cured in the silicone oil. The small balls are cured in the silicone oil for 1h;

[0052] Step 5, washing and roasting: take out the solidified small balls from the silicone oil and put them into anhydrous ethanol for washing. The number of times the small balls are washed is 3-4 times, and the washing time for each time is 8min-12min; then, put the washed small balls into a muffle furnace for roasting. The muffle furnace is preheated to 300°C for roasting. The roasting time is 1h to remove the silicone oil in the pores of the small balls. After the roasting is completed, turn off the power of the muffle furnace and let the small balls cool naturally to room temperature in the furnace;

[0053] Step 6: Final washing: The calcined pellets are placed in deionized water for soaking and washing. After the soaking and washing is completed, the pellets are taken out from the deionized water and dried naturally to finally obtain spherical porous regenerated micropowder-fly ash geopolymer.

[0054] In the present invention, firstly, the regenerated micropowder is carbonized, and the raw materials are mixed, sphericalized, solidified, washed and roasted according to proportions and conditions, so as to prepare a spherical porous regenerated micropowder-fly ash geopolymer; not only can the resource utilization of waste concrete regenerated micropowder be realized, and the problem that the regenerated micropowder is difficult to utilize can be solved, but also the porous structure and chemical composition of the material, such as the components such as hydrated calcium silicate gel and calcium hydroxide in the regenerated micropowder, can also effectively improve the utilization of Pb 2+ The adsorption effect can achieve the treatment of Pb 2+ The purpose of the pollution;

[0055] In addition, during the preparation process, the carbonized regenerated micropowder and fly ash are combined for the second time. The reaction mechanism is to use NaOH and water glass as activators to make the carbonized regenerated micropowder and fly ash react to form geopolymers. At the same time, K12 and silicon slag as foaming agents produce gas to reduce the density of the slurry. After the silicone oil is dripped into the slurry, the surface tension is used to form balls, and the geopolymer undergoes a rapid polycondensation reaction and solidification at high temperature; the chemical reaction formula is the reaction of silicon slag: Si+2H2O+2MOH→M2Si2(OH)2+2H2↑. The geopolymers prepared by these reactions can achieve the purpose of Pb 2+ Effective remediation of pollution and resource utilization of recycled micropowder and silicon slag can achieve the effect of "using waste to treat pollution".

[0056] according to Figure 2 and Figure 3 As shown in Figure 2, the material exhibits a layered gel structure, and this structure is full of continuous pores. 2+ The presence of pores greatly increases the specific surface area of ​​the material, enabling it to provide more active sites for Pb adsorption. 2+ When Pb 2+ When the solution of Pb comes into contact with the material, 2+Ions can enter these pores through diffusion and interact with active groups on the pore walls, thus achieving the adsorption process;

[0057] In addition, elemental analysis (EDS) shows that the Si element of the spherical porous regenerated micropowder-fly ash geopolymer is 40.1wt%, the Al element is 7.4wt%, the Ca element increases to 47.1wt%, and there is also Na element; among them, the Si element and the Al element mainly come from the aluminosilicate minerals in the fly ash and regenerated micropowder; in the process of geopolymerization, these elements form the skeleton structure of the geopolymer through the recombination of chemical bonds; the high content of the Ca element is related to the calcium hydroxide in the regenerated micropowder, and the calcium hydroxide participates in the reaction under an alkaline environment, affecting the pore structure and chemical properties of the material; the Na element comes from the activator sodium hydroxide, which plays a role in promoting the geopolymerization reaction during the reaction.

[0058] according to Figure 4 As shown in the figure, through X-ray crystal diffraction (XRD) analysis, on the one hand, the material exhibits amorphous characteristics, indicating that during the preparation process, the raw materials underwent complex chemical reactions to form amorphous geopolymers; the formation of the amorphous structure is due to the fact that during the high-temperature rapid polycondensation reaction, the atoms in the raw materials do not have enough time to arrange in order; this amorphous structure has high chemical activity and disorder, so that there are a large number of unsaturated bonds and active sites on the surface of the material, which can react with Pb 2+ Strong interactions occur between heavy metal ions, which is beneficial to the adsorption process;

[0059] On the other hand, CSH characteristic peaks appear at 20°-40°, indicating that fly ash and recycled micropowder have been transformed into geopolymers. CSH gel is an important component of geopolymers. It has good gelling properties and certain ion exchange capacity, which helps to fix the pore structure of the material and provides a good source of Pb 2+ The adsorption provides certain chemical active sites;

[0060] In addition, the appearance of the Ca(OH)2 diffraction peak indicates that there is an excess of regenerated micropowder in the preparation process, and some regenerated micropowder did not fully participate in the geopolymerization reaction. However, combined with the comprehensive analysis of EDS and XRD data, it can be confirmed that the spherical porous regenerated micropowder-fly ash geopolymer has been successfully prepared. At the same time, Ca(OH)2 itself is alkaline, and during the adsorption process, it can react with Pb 2+ Chemical reactions occur to form insoluble lead compounds, which help Pb 2+ removal.

[0061] The specific surface area, pore size distribution and pore volume parameters of the material are determined by measuring the adsorption-desorption isotherm of gas (nitrogen) on the material surface. The prepared spherical porous regenerated micropowder-fly ash geopolymer sample is pretreated, usually by heating under vacuum or inert atmosphere to remove impurities and moisture adsorbed on the sample surface; then, the treated sample is placed in a BET specific surface area analyzer, and the relative pressure of nitrogen is gradually changed at liquid nitrogen temperature (-196°C), and the adsorption and desorption amounts of nitrogen at different relative pressures are measured to obtain the adsorption-desorption isotherm.

[0062] Table 1 BET analysis of materials

[0063]

[0064] pass Figure 5 As shown in Table 1, the specific surface area is 77.89 m 2 / g, and the total pore volume is 0.18 cm 3 / g; high specific surface area and appropriate pore volume make the material have good adsorption performance; large specific surface area is conducive to more adsorption sites on the material surface for Pb 2+ ion attachment, and the appropriate pore volume can ensure Pb 2+ Ions can effectively diffuse into the material to achieve efficient adsorption; and Figure 5 The inset diagram (pore radius distribution determined by the BJH method) can further understand the pore structure characteristics of the material. This pore radius distribution can directly affect the material's resistance to Pb 2+ Adsorption kinetics and adsorption capacity;

[0065] Specifically, the pores in the material include different types of micropores, mesopores, and macropores, which are interconnected to form a favorable 2+ The pore network of adsorption and diffusion; micropores can provide strong adsorption sites, mesopores facilitate the rapid diffusion of ions, and macropores can serve as channels for ion transmission, which work together to increase the material's Pb 2+ Effect of adsorption process.

[0066] In order to understand the material's effect on Pb 2+ The rate-controlling step and mechanism of the adsorption process, therefore, by comparing the fitting results of the pseudo-first-order kinetics and pseudo-second-order kinetics models, it can be determined whether the adsorption process is physical adsorption (pseudo-first-order kinetics, mainly controlled by diffusion) or chemical adsorption (pseudo-second-order kinetics, involving electron sharing or electron transfer between adsorbent and adsorbate), and by the following operations:

[0067] Firstly, the spherical porous recycled micro-powder-fly ash geopolymer material was mixed with a known concentration of Pb 2+The solution was fully contacted at 25℃-50℃; after a long time to reach adsorption equilibrium, the Pb 2+ The concentration of Pb 2+ The amount minus the remaining Pb 2+ The amount of Pb 2+ The equilibrium adsorption capacity was 59.6 mg / g. Then, the adsorption kinetics experiment was carried out to measure the adsorption of Pb by taking samples at different time points. 2+ The adsorption amount at different time points included 10min, 20min, 30min, 40min, 50min and 60min, and was substituted into pseudo-first-order kinetics and pseudo-first-order kinetics for calculation respectively.

[0068] Table 2 Materials adsorbing Pb 2+ The kinetic model parameters

[0069]

[0070] According to Table 2, the correlation coefficient (R 2 =0.991) is higher than the pseudo-first-order kinetic model (R 2 =0.983), and the equilibrium adsorption amount (62.3 mg / g) calculated by the pseudo-second-order kinetic model was closer to the experimental value (59.6 mg / g), which indicated that the adsorption process was more inclined to chemical adsorption.

[0071] Since adsorption isotherm studies can reveal the properties of the adsorbent surface and the interaction between the adsorbate and the adsorbent; different isotherm adsorption models are suitable for different adsorption surfaces and adsorption mechanisms. For example, the Langmuir model can determine whether the adsorption is a monolayer adsorption and can obtain the maximum adsorption amount of the material, which is beneficial for the material to be used in the treatment of Pb 2+ The treatment capacity of the adsorbent is evaluated when it is contaminated; the Freundlich model is applicable to multilayer adsorption on non-uniform surfaces and can reflect the heterogeneity of the adsorbent surface and the interaction between the adsorbates;

[0072] Table 3 Materials adsorbing Pb 2+ Langmuir and Freundlich model parameters

[0073]

[0074] In Table 3, the correlation coefficient of the Langmuir model (R 2 =0.980) is higher than the Freundlich model (R 2 =0.911), and the maximum adsorption capacity (Q m=108.5 mg / g) is close to the experimental value (104.7 mg / g), indicating that the adsorption process is more consistent with the monolayer adsorption mechanism.

[0075] It can be seen from the data in Table 2 and Table 3 that the spherical porous recycled micropowder-fly ash geopolymer material has a significant effect on Pb 2+ adsorption characteristics.

[0076] The spherical porous regenerated micropowder-fly ash geopolymer is prepared by carbonizing the regenerated micropowder and mixing it with fly ash and other raw materials. This is not only conducive to the resource utilization of waste resources, avoiding the waste of resources, but also reducing the pressure that these wastes may cause to the environment. At the same time, it effectively improves the stability and efficiency of adsorption, and can efficiently remove Pb 2+ It is removed from water bodies, achieving the environmental protection goal of "using waste to treat pollution", thereby improving the health of the environment and humans.

[0077] Effect of spherical porous recycled micropowder-fly ash geopolymer on Pb 2+ It has good adsorption effect. Its layered gel structure is densely covered with continuous pores, which greatly increases the specific surface area and provides more active sites. In addition, the carbonization treatment improves the regenerated micropowder's adsorption of Pb 2+ Active sites, during the adsorption process, the chemical composition and structural characteristics of the material can effectively adsorb Pb 2+ , reducing the cost of materials, not only can it achieve the effective utilization of recycled micro-powder from waste concrete, but it can also transform the original waste into an adsorbent that is beneficial to environmental governance, realizing the “turning waste into treasure”, thereby improving the utilization rate of waste resources and the efficiency of environmental restoration.

[0078] In order to verify that the recycled concrete powder prepared in the embodiment of the present invention has good adsorption and stability for porous geopolymer materials, the recycled concrete powder provided in the embodiment of the present invention for porous geopolymer materials is described through the following test examples.

[0079] Test example

[0080] The purpose of this test group is to study the effects of different factors on the adsorption of Pb by spherical porous recycled micropowder-fly ash geopolymer materials. 2+ Quantity (Q e ), the different factors include water glass modulus, recycled micro powder content, silicon slag content and water glass content.

[0081] Test objective: To determine the effect of various factors on the adsorption capacity Q e The influence degree of adsorption is found to make the adsorption amount Q e The factor level combinations that reach the maximum value are: water glass modulus, recycled micro powder content, silicon slag content and water glass content are A, B, C and D respectively.

[0082] Experimental methods: factor level design, experimental operation and data analysis; among which:

[0083] Factor level design:

[0084] Factor A: set three levels, namely 1.3, 1.4, and 1.5;

[0085] Factor B: three levels were set, namely 15wt%, 20wt%, and 25wt%;

[0086] Factor C: three levels were set, namely 0.3wt%, 0.4wt%, and 0.5wt%;

[0087] Factor D: three levels were set, namely 0.5wt%, 1.0wt%, and 1.5wt%;

[0088] Experimental operation:

[0089] According to the orthogonal experimental design, a total of 9 groups of experiments were conducted, and each group of experiments was used to prepare spherical porous recycled micropowder-fly ash geopolymer according to different factor level combinations, for example:

[0090] Experiment 1: A = 1.3, B = 15wt%, C = 0.3wt%, D = 0.5wt%, measured adsorption amount Q e =44.30mg / g;

[0091] Experiment 2: A = 1.3, B = 20wt%, C = 0.4wt%, D = 1.0wt%, the adsorption amount Q was measured e =39.11 mg / g;

[0092] And so on, 9 sets of experiments were conducted;

[0093] Data Analysis:

[0094] Calculate the sum (K1, K2, K3) and average (k1, k2, k3) of the adsorption amount of each factor at different levels:

[0095] For example, the sum of adsorption amounts corresponding to the three levels of factor A are K1 (the sum of adsorption amounts of three groups of experiments at the 1.3 level), K2 (the sum of adsorption amounts of three groups of experiments at the 1.4 level), and K3 (the sum of adsorption amounts of three groups of experiments at the 1.5 level). Similarly, calculate the K values ​​of factors B, C, and D;

[0096] Calculate the average adsorption amount of each factor at different levels (k1, k2, k3):

[0097] For example, k1 of factor A = K1 / 3 = 137.61 / 3 = 45.87; and so on, calculate the k values ​​of other levels;

[0098] Calculate the range R, which is the difference between the maximum and minimum values ​​of the average adsorption amount at different levels of each factor:

[0099] For example, R of factor A = 53.78 - 45.87 = 7.91.

[0100] Specific detection indicators are shown in Table 4.

[0101] Table 4 Orthogonal experiment data analysis calculation table

[0102]

[0103]

[0104] According to Table 4, RA>RC>RD>RB, that is, the decisive factor affecting the experiment is A-water glass modulus, followed by C-recycled micro powder content. And the optimal factor level conditions of this experiment are A2B2C3D1, that is, water glass modulus is 1.4M, recycled micro powder content is 20wt%, silicon slag content is 0.5wt%, and water glass content is 0.5wt%.

[0105] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing porous geopolymer material using recycled concrete powder, characterized in that: The following steps are involved: S1. Preparation of carbonized regenerated micropowder: placing the regenerated micropowder in a tube furnace, then introducing a CO2 atmosphere with a concentration exceeding 99.5% into the tube furnace, opening the tube furnace for roasting, and after the roasting is completed, closing the carbon dioxide gas source, and taking out the powder after naturally cooling it to room temperature in the tube furnace to obtain carbonized regenerated micropowder; S2. Raw material preparation: carbonized regenerated micro powder; fly ash; liquid sodium silicate; sodium hydroxide; distilled water; foaming agent; modulus adjustment; S3, raw material mixing: fly ash, carbonized regenerated powder, liquid sodium silicate, sodium hydroxide, distilled water and foaming agent are added to a stirring container in sequence, and the stirring container is opened to stir and mix to obtain a mixed slurry; S4, balling and solidification: Turn on the water bath device for heating, and prepare a container for silicone oil. Then, use a syringe to drop the mixed slurry into the silicone oil to make it into small balls with uniform shape, and solidify the small balls in the silicone oil; S5, washing and calcining: taking the solidified balls out of the silicone oil, washing them in anhydrous ethanol, and then calcining them in a muffle furnace to remove the silicone oil in the pores of the balls. After calcining, turning off the power of the muffle furnace and allowing the balls to cool naturally to room temperature in the furnace; S6. Final washing: The calcined pellets are placed in deionized water for soaking and washing. After the soaking and washing is completed, the pellets are taken out from the deionized water and dried naturally to finally obtain spherical porous regenerated micropowder-fly ash geopolymer.

2. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: In S1, after the temperature of the tube furnace is raised to 300°C, the calcination is continued for 2 hours.

3. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: The S2 includes the following raw materials: Carbonized regenerated micro powder: The dosage of carbonized regenerated micro powder is 3g-5g; Fly ash: The amount of fly ash is 5g-7g; Liquid sodium silicate: The dosage of liquid sodium silicate is 1.5g-2.5g; Sodium hydroxide: The dosage of sodium hydroxide is 0.15g-0.27g; Distilled water: The amount of distilled water used is 1.1ml-2.2ml; Foaming agent: Mix silicon slag and K12 in a dry and clean environment. The amount of silicon slag is 0.3g-0.5g, and the amount of K12 is 0.035g-0.045g; Modulus adjustment: M=1.

4.

4. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: In S3, the stirring speed of the stirring container is 180r / min-240r / min, and the stirring time is 20min-30min.

5. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: In S4, the water bath is heated to 75°C.

6. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: In the above S4, the injection speed of the syringe into the mixed slurry is 0.5ml / min-1ml / min.

7. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: In S4, the beads are cured in silicone oil for 1 h.

8. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: In S5, the beads are washed 3 to 4 times, and each washing time is 8 to 12 minutes.

9. The method for preparing porous geopolymer material using recycled concrete powder according to claim 1, characterized in that: In S5, the muffle furnace is preheated to 300° C. for calcination, and the calcination time is 1 hour.

10. An application of recycled concrete powder for porous geopolymer materials, characterized in that: The spherical porous regenerated micropowder-fly ash geopolymer obtained by the method for preparing the porous geopolymer material using the regenerated concrete micropowder according to claim 1 is used to treat Pb in the environment. 2+ pollute.